Assessing the association between menstrual cycle phase and voice-gender categorization: no robust evidence for an association - Friedrich, Sarah; Brodkin, Edward S.; Derntl, Birgit; Habel, Ute; Hüpen, Philippa (Frontiers in Psychology, 2025)
IntroductionHormone fluctuations during the menstrual cycle are known to influence a wide variety of cognitive-emotional processes and behavior. Mate choice and changes in attractiveness ratings for faces and voices are often investigated in this context, but research on changes in voice-gender perception independent of attractiveness ratings is rare even though the voice is an essential element in social interactions. For this reason, we investigated the influence of cycle phase and levels of estrogen and progesterone on performance in a voice-gender categorization task. Our expectation was to find a more pronounced other-sex effect, so faster and more accurate reactions for masculine voices, in the follicular (fertile) phase than in the luteal phase.MethodsWe measured 65 healthy, naturally-cycling women, half of them in the follicular phase and the other half in the luteal phase. For the analyses, we used signal detection theory (SDT) measures in addition to reaction times and percent of correct reactions. The study was preregistered after measuring the first 33 participants and prior to any data analyses (https://osf.io/dteyn).ResultsCycle phase and hormone levels showed no significant effect on reaction time or SDT measures. This was the case both using frequentist analyses and Bayesian statistics. Reaction time was influenced by voice-gender, with faster reactions for feminine voices compared to masculine voices in both cycle phases.DiscussionTaken together, our results add to the increasing number of studies that do not find an interaction of menstrual cycle phase and reaction to gendered stimuli.